Retention in HIV care and associated factors among youths aged 15-24 years in rural southwestern Uganda - Moses Muwanguzi; Henry Mark Lugobe; Elastus Ssemwanga; Allan Phillip Lule; Elizabeth Atwiine; Vincent Kirabira; Ann K. Stella; Scholastic Ashaba; Godfrey Zari Rukundo (BMC, 2021)
Abstract Background Retention in HIV care contributes to antiretroviral therapy adherence, which is a key factor for improved treatment outcomes and prevention of drug resistance. However, HIV treatment among the youths is characterized by loss to follow up, poor adherence to ART, risk of treatment failure and high mortality rates compared to young children and adults. There is limited information about factors associated with retention of youths in HIV care in rural settings in Uganda. We aimed to determine retention in HIV care and associated factors among youths aged 15-24 years in rural southwestern Uganda. Methods A cross-sectional study was conducted among youths aged 15-24 years who were receiving care at the HIV clinic at Kabuyanda HC IV who had been in care for at least 1 year before the study. We used an interviewer-administered questionnaire to collect socio-demographic information. Participant chart abstraction was used to collect information on HIV clinic attendance. We collected information on HIV related stigma using the 40-item Berger Stigma Scale. Chi-square test and multivariable logistic regression analysis were used to determine the factors associated with retention in HIV care with a significance level of < 0.05. Retention in HIV care was, defined as having sought care at least once per quarter in the 12 months prior to the study. Results We enrolled 102 participants with a mean age of 20.95 (SD ± 3.07) years. Two thirds (65.7%) of the youths had been retained in HIV care in the previous 12 months. In adjusted analyses, being male, married and had perinatally acquired HIV were independently associated with retention in HIV care. The association between HIV related stigma and retention in HIV care was not statistically significant. Conclusion Retaining adolescents and young adults in HIV care in rural southwestern Uganda is still much lower than the WHO target of 90%. Being male, having perinatally acquired HIV and married or in a relationship are associated with retention in HIV care. Interventions targeting adolescents and young adults living with HIV are necessary to improve retention in HIV care to the WHO target of 90%.